MENAKAR KEKUATAN DAN KEUNGGULAN INDUSTRI TELEVISI LOKAL DI ERA OTONOMI - Priyowidodo, Gatut (Scriptura, 2008)
The development of industrial television has two sides. In one hand, it gives blessing but on the other hand posses some disadvantages. In autonomy era since 1999, all regional administratives have big opportunities to establish television station. Therefore, they are competing to invite some investors to come. Such as, Bali Post from Bali found Yogya TV, Jawa Pos came to Batam and found Batam TV etc. They are aware that it isn?t difficult to manage media firm. TV has more influence than radio or print media. Since 1950, all country in the world had used TV as media to campaign or to socialize their program to people. TV is an effective tool to deliver message to audience. Basicaly, human prefers audio-visual activity than to read or to listen. Through TV, they can take information, entertainment, and also education values. By 2009, there will be more than two hundred television stations established in some cities in Indonesia. Finally, the audiences will have more channels to watch.